A survey of students' preferences for research paper / Sumardi Sungit and Yvonne Eliza Mroon - Sungit, Sumardi; Mroon, Yvonne Eliza (2005)
Each individual has different perceptions of research paper. Some students think that conducting a research paper was a good experience and some perceive it as a burden. In this project, we studied students preference toward research paper.